A New Method for Auto-calibrated Object Tracking - Duff, Paul; McCarthy, Michael; Clark, Angus; Muller, Henk; Randell, Cliff; Izadi, Shahram; Boucher, Andy; Law, Andy; Pennington, Sarah; Swinford, Richard (Proceedings of the 7th International Conference on Ubiquitous Computing (UbiComp 2005), 2005)
Ubiquitous computing technologies which are cheap and easy to use are more likely to be adopted by users beyond the ubiquitous computing community. We present an ultrasonic-only tracking system that is cheap to build, self-calibrating and self-orientating, and has a convenient form factor. The system tracks low-power tags in three dimensions. The tags are smaller than AAA batteries and last up to several years on their power source. The system can be configured to track either multiple near-stationary objects or a single fast moving object. Full test results are provided and use of the system within a home application is discussed.